Leaving Home: Refugee Trauma In Afghanistan And Syria In Melissa Fleming’s A Hope More Powerful Than The Sea And Siba Sakib’s Afghanistan Where God Only Comes To Weep - Kalita, Popi; K. Moral, Rakhee (Journal of Neonatal Surgery, 2025)
Home is an abode embedded with emotion, a vista of moments and memories with feelings of love towards one another. The ‘home’ is one’s origin and a place of one’s formation of culture and identity. Very often, the contemplation and the inevitability of distancing the self from one’s home traumatizes one with questions of security, individuality and originality. However, the idea of ‘home’ enormously conveys meanings and implications in depth when a ‘refugee’ comes into the deliberation. For a refugee, leaving home is immensely traumatic, as once left, retrieving the home becomes infeasible. Melissa Fleming’s A Hope More Powerful Than the Sea (2017) and Siba Sakib’s Afghanistan Where God Only Comes to Weep (2002) delineate notions regarding how people from Syria and Afghanistan respectively have turned aliens in their own home. This paper aims to understand and look into the trauma that a refugee undergoes while leaving their homes thereby, embarking into a life of exile and attempting to relocate ‘home’.